Intervenciones de enfermería en pacientes con Parkinson - Obando Contento, José Luis (Machala : Universidad Técnica de Machala, 2021)
Parkinson's disease is a chronic neurodegenerative pathology that damages the nervous system causing the progressive loss of neurons which contain dopamine, its symptoms are bradykinesia, tremor at rest, rigidity, postural problems, language problems and difficulty swallowing. This disorder appears between the age of 50 to 80 years being influenced by some environmental factors, race, gender and age. In the world, it has a prevalence of 100 - 300 cases per 100,000 inhabitants and an incidence between 1.5-22 for all ages, placing Parkinson's as the second neurodegenerative disease with the highest prevalence in the world. In Ecuador, no statistical data were found on the incidence or prevalence of this pathology, although a study carried out in the province of Manabí in 2017, gave the prevalence of 243 cases per 100,000 inhabitants over 61 years of age, being more frequent in males than the feminine. The objective is to determine the nursing interventions through the bibliographic review in patients with Parkinson's for the implementation of the nursing care process.
La Enfermedad de Parkinson es una patología neurodegenerativa crónica que perjudica al sistema nervioso ocasionando la pérdida progresiva de neuronas las cuales contienen dopamina, sus síntomas son la bradicinesia, temblor de reposo, rigidez, problemas posturales, problemas de lenguaje y dificultad para deglutir. Este trastorno aparece entre la edad de 50 a 80 años siendo influenciado bajo algunos factores ambientales, raza, género y edad. En el mundo presenta la prevalencia de 100 – 300 casos por cada 100.000 habitantes y la incidencia entre 1.5-22 para todas las edades, colocándolo al Parkinson como la segunda enfermedad neurodegenerativa con mayor prevalencia en el mundo. En Ecuador no se encontraron datos estadísticos sobre incidencia o prevalencia de esta patología, aunque un estudio realizado en la provincia de Manabí en el 2017, dio como prevalencia 243 casos por cada 100.000 habitantes mayores de 61 años, siendo más frecuente en el sexo masculino que el femenino El objetivo es determinar las intervenciones de enfermería a través de la revisión bibliográfica en pacientes con Parkinson para la implementación del proceso de atención de enfermería.
Keywords: PARKINSON; NEURODEGENERATIVA; TRASTORNOS DEL MOVIMIENTO; ENFERMERIA